Experimental complex for studying the physical properties of artificially formed gas hydrate containing sediments - Kobolev, V.P.; Mikhailyuk, S.F.; Safronov, A.M. (Reports of the National Academy of Sciences of Ukraine, 2022)
The presence of gas hydrates in marine bottom sediments significantly changes their physical properties, so they can be detected by remote geophysical observations. Physical properties of gas hydrate-containing sediments (HCS) are extremely important information for detecting the presence of these compounds, estimating the amount of captured gas hydrates by sediments, as well as developing methods for using this resource. Currently, the study of physical properties concerned mainly artificial gas hydrates in the process of formation and decomposition under various thermodynamic conditions in their pure form. Therefore, very little is known about the physical properties of HCS, which makes their detection by remote geophysical surveys too difficult. Development and creation of experimental laboratory modular complex for formation and measurement of physical properties of artificial methane gas hydrates in various lithological-granulometric matrices (sandstones, argillites, siltstones, etc. ) will increase efficiency geophysical methods of their exploration and optimize of technology of methane hydrate deposits development.